1982
DOI: 10.1079/bjn19820142
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the range of tissue protein synthesis in pigs: the effect of thyroid hormones

Abstract: 1. The effects of thyroid hormones on the range of tissue protein synthesis in growing pigs using the constant infusion technique with [14C]leucine and [I4C]lysine were studied.2. During a 6 h infusion, samples were taken from blood and, at the end of the infusion, from liver, pancreas, stomach, small and large intestines, kidney cortex, kidney medulla, muscle and skin.3. Lower relative specific radioactivities of free leucine and lysine in several tissues were observed in the hormone-treated group than in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…Expressing visceral organ mass as grams per kilogram of empty body weight, resulted in similar responses. The major effect of high-Se wheat on visceral organ mass occurred in jejunal tissue, which is one of the most metabolically active tissues among those evaluated in this study (Simon et al, 1982). In general, visceral organs are very active metabolically and represent a substantial amount of maintenance energy consumption (Caton et al, 2000).…”
Section: Resultsmentioning
confidence: 80%
“…Expressing visceral organ mass as grams per kilogram of empty body weight, resulted in similar responses. The major effect of high-Se wheat on visceral organ mass occurred in jejunal tissue, which is one of the most metabolically active tissues among those evaluated in this study (Simon et al, 1982). In general, visceral organs are very active metabolically and represent a substantial amount of maintenance energy consumption (Caton et al, 2000).…”
Section: Resultsmentioning
confidence: 80%
“…Taking into account that both extracellular amino acids originating from plasma or digesta and intracellular amino acids derived from intracellular protein degradation are used for protein synthesis (Simon et al, 1982(Simon et al, , 1983 and that endogenous N in the gut lumen is derived from multiple precursor pools (Moughan et al, 1992), the ,5 N-enrichment in urinary N was used as an indicator of that in endogenous N during a steady state after withdrawal of 15 NH 4 C1. At this time, the 15 N in urine originated only from the catabolism of 15 N-labelled body protein.…”
Section: Methodical Aspectsmentioning
confidence: 99%
“…There were no treatment effects on total DNA, protein concentration or protein/DNA ratio in the small intestine, which indicated that there were no increases in the number or size of cells per unit of tissue in response to the replacement of lactose with rice syrup. Previous studies have reported that a high rate of energy expenditure by the gastrointestinal tract is associated with high rates of cell turnover and protein synthesis in these tissues 42–47. Thus factors that influence the rate of turnover of intestinal epithelial cells may strongly influence the efficiency of whole‐body energy utilisation.…”
Section: Discussionmentioning
confidence: 99%